Global Competence in Canadian Teacher Candidates - Sokal, Laura; Parmigiani, Davide (Frontiers in Education, 2022)
The purpose of the study was to determine the global competence of 115 Canadian teacher candidates using a new measurement tool. Non-parametric tests indicated several differences in self-reported global competence within individual indicators across the three areas of Exploring, Engaging, and Acting with global competence. Two indicators showed that male teacher candidates reported higher levels of global competence than did females in the Exploring and Acting areas. Teacher candidates intending to teach in middle and senior high school reported higher levels in one indicator within the Acting area. Moreover, Canadian-born teacher candidates reported higher levels of Engaging and Acting than did non-Canadian-born students across six indicators total. While there were no differences across the three areas by age, results showed that higher levels of experience in their teacher education program were associated with greater global competence across all three areas as indicated by five indicators total, with three at the Acting stage. Implications for teacher education are discussed.